PAINFUL NEURALGIA RELATED RAMSAY HUNT SYNDROME: A CASE REPORT - Pinzon, Rizaldy Taslim; Pandita, Felicia Dara Puspitaning (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Ramsay Hunt Syndrome is a rare case. This syndrome is a severe complication of the reactivation of varicella zoster virus in the geniculate ganglion. Facial paralysis is the main clinical presentation. We present a rare case Ramsay Hunt Syndrome in a 48 year old female that referred to neurology clinic with very painful herpetic neuralgia, left ear discomfort, and facial palsy. The patient came after two weeks eruption of herpetic rash in the second and third branch of trigeminal nerve. Treatment as antiviral, steroid, gabapentin, and amitriptyline showed improvement and significantly reduced the pain in this patient.